Attenuation of the pro-inflammatory signature of lung cancer-derived mesenchymal stromal cells by statins. (1st August 2020) - Galland, Sabine; Martin, Patricia; Fregni, Giulia; Letovanec, Igor; Stamenkovic, Ivan
Abstract: Solid tumor growth triggers a dynamic host response, which recapitulates wound healing and defines the tumor microenvironment (TME). In addition to the action of the tumor cells themselves, the TME is maintained by a myriad of immune and stromal cell-derived soluble mediators and extracellular matrix components whose combined action supports tumor progression. However, therapeutic targeting of the TME has proven challenging because of incomplete understanding of the tumor-host crosstalk at the molecular level. Here, we investigated the crosstalk between mesenchymal stromal cells (MSCs) and primary cancer cells (PCCs) from human squamous cell lung carcinoma (SCC). We discovered that PCCs secrete CCL3 and stimulate IL-6, CCL2, ICAM-1 and VCAM-1 expression in MSCs and that the MSC-PCC crosstalk can be disrupted by the lipid-lowering drug simvastatin, which displays pleiotropic effects on cell metabolism and suppresses IL-6 and CCL2 production by MSCs and CCL3 secretion by PCCs. In addition, simvastatin inhibited spheroid formation by PCCs and negatively affected PCC survival. Our observations demonstrate that commonly used statins may be repurposed to target the TME in lung carcinoma. Highlights: The squamous lung carcinoma microenvironment harbours pro-inflammatory features. Mesenchymal stromal cells (MSCs) engage in tumor-promoting crosstalk with cancer cells. Primary lung carcinoma cells (PCCs) produce CCL3 and enhance MSC secretion of IL-6 and CCL2. Simvastatin disrupts MSC-PCC crosstalk. Statins can be repurposed to target the lung cancer microenvironment.